Figurative Language Analysis in Selected Maroon 5 Songs - Erlita Audina Ma'rifa; Yuli Astutik (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the figurative language in the Maroon 5 Selected Song. In this study, the authors analyzed the song lyrics of nine songs belonging to Maroon 5, namely Shiver, Goodnight goodnight, The way i was, Moves like jagger, Can't stop, Sweetest goodbye, Until you're over me, Ragdoll, and Woman. In this study the authors used qualitative methods. The data source used was the Maroon 5 singer with several selected songs. The data is taken in the figurative language used in the lyrics of the Maroon 5 song. Sources of data are taken from sources on the website in the form of Maroon 5 band song lyrics. The researcher can conclude that in the maroon 5 song there are seven types of figurative language. The figurative language meanings found in the song Maroon 5. Mostly represent what actually happened in the lives of the Maroon 5 members. He didn't write it down in a real sense. He uses figurative language to share his feelings. Contradictory figurative language is the dominant figurative language in Maroon 5's song. The type of figurative language he uses most is hyperbole.